Implementation of Zhu Takaoka Algorithm in Android-Based Restaurant Mobile Applications - Abdul Wahab Nainggolan; Guidio Leonarde Ginting (STMIK Budi Darma, 2020)
Competition of fast food restaurants at this time is getting tougher, this can be seen from the development of several fast food restaurants or fast food restaurants that exist, including Kentucky Fried Chicken, California Fried Chicken, Mc Donalds, New York Chicken, and Texas Chicken. This makes all restaurants competing in attracting consumers to buy products from the restaurant. Various efforts have been made ranging from opening branches, offering saving packages to consumers, and adding new types of food. Fast food can be interpreted as food that can be prepared to be served and consumed in a short time and can be eaten quickly. Ordering food and drinks is preferred at the current restaurant. The process of choosing food and beverage menus that are currently running at Garuda restaurants is still using menu books, menu books containing a large number of food and beverage menus, many menus are a problem for consumers because consumers find it difficult to find food and beverage menus quickly. And for the way to choose the menu itself, still see the list of food and beverage menu